SOME OF THE PROBLEMS OF LEGISLATIVE PROVISION OFOPERATIONAL-SEARCH ACTIVITIES AND THEIRSOLUTIONS - Khamdamov , Abduvali (Eurasian Journal of Academic Research, 2022)
The article discusses the actual problems of legislative provision of the basis for conductingoperational-search activities. The author made a proposal on amendments and additions to Article15 of the law“on operational-search activity” on the basis of conducting operational-searchactivities.